Correlates of Informal Grievance Resolution Among Fist-Line Supervisors - Knight, Thomas (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1986)
This study analyzes the influence on the rate of informal grievance resolution of differences in experience and interaction with union and other management officers of a sample of first line supervisors